Campur Kode Bahasa Arab dalam Ceramah Gus Baha pada Acara Maulidyah dan Harlah ke 52 PP. Al-Anwar, 06 Rabi'ul Awwal 1440 H/14 November 2018 : Sosoilinguistik, Campur Kode - Septian Pratama (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
The development of technology makes a lecture from an ustadz in an area accessible to Muslim communities in any area, for example through the YouTube application. However, The Ustadz uses the local language, so that netizens from other regions who want to listen to the lecture have difficulty understanding the contents of the lecture. The most obvious example is KH. Ahmad Bahauiddin Nursalim, or Gus Baha. The researcher tries to describe how the code mixing process, which is specific to the Arabic language that Gus Baha uses. The approach used in this study is adescriptive approach approach, while the method used is qualitative. The object of the research was Gus Baha's video lecture with the theme “Mengupas Pendidikan Keagamaan di Zaman Sekarang Untuk Pesantren dan Masyarakat”. The reason why Gus Baha used mixed Arabic codes very much in the lecture was because he was in the presence of the Ustadzs and students of PP. Al-Anwar who is almost the majority of them unders The development of technology makes a lecture from an ustadz in an area accessible to Muslim communities in any area, for example through the YouTube application. However, The Ustadz uses the local language, so that netizens from other regions who want to listen to the lecture have difficulty understanding the contents of the lecture. The most obvious example is KH. Ahmad Bahauiddin Nursalim, or Gus Baha. The researcher tries to describe how the code mixing process, which is specific to the Arabic language that Gus Baha uses. The approach used in this study is adescriptive approach approach, while the method used is qualitative. The object of the research was Gus Baha's video lecture with the theme “Mengupas Pendidikan Keagamaan di Zaman Sekarang Untuk Pesantren dan Masyarakat”. The reason why Gus Baha used mixed Arabic codes very much in the lecture was because he was in the presence of the Ustadzs and students of PP. Al-Anwar who is almost the majority of them understand Arabic. The conclusion of this study is that lecturers must be able to understand the characteristics of their audience, so that they will use language that is able to be captured by the audience. One of the factors that influence the use of code mixing is the interlocutor. So even though the communication speech formed is mostly one-way communication, the audience is the speaker. Keywords: code mix, Lecture, Gus Baha, Arabic tand Arabic. The conclusion of this study is that lecturers must be able to understand the characteristics of their audience, so that they will use language that is able to be captured by the audience. One of the factors that influence the use of code mixing is the interlocutor. So even though the communication speech formed is mostly one-way communication, the audience is the speaker. Keywords: code mix, Lecture, Gus Baha, Arabic